The effect of toxic leadership on workplace deviance: the mediating effect of emotional exhaustion, and the moderating effect of organizational cynicism - Asmaa Kamal Ahmed; Mohamed Hussein Ramadan Atta; Ahmed Hashem El-Monshed; Alia Ibrahim Mohamed (BMC, 2024)
Abstract Background Toxic leadership is abusive, destructive, and detrimental to nurses, can decrease nurse morale, increase stress levels, diminish organizational performance, and cause employee emotional exhaustion. Emotional exhaustion, a key component of burnout, has been linked to decreased job performance and increased likelihood of engaging in deviant behaviors at work. Organizational cynicism, as a negative attitude or distrust towards the organization and its leadership, may exacerbate the relationship between toxic leadership and workplace deviance. This study aims to explore how toxic leadership, workplace deviance, emotional exhaustion, and organizational cynicism are interrelated in the nursing profession. Method A multicenter descriptive, cross-sectional research design was conducted at three university hospitals affiliated with three Egyptian governorates: Zagazig, El-Fayoum, and Alexandria. Two hundred forty-three nurses completed the Personal and Job-related Data Questionnaire, Toxic Leadership Scale, Emotional Exhaustion Scale, Workplace Deviance Scale, and Organizational Cynicism Scale. Mediation analysis using SPSS PROCESS revealed that emotional exhaustion indirectly influences the relationship between toxic leadership and workplace deviance, while hierarchical multiple regression showed that organizational cynicism moderates this relationship, with linear regression confirming the predictive impact of these variables on workplace deviance. Results Toxic leadership exhibits a substantial positive influence on workplace deviance (B = 16.132, p < 0.001), as does emotional exhaustion (B = 8.760, p < 0.001) and organizational cynicism (B = 5.376, p = 0.036). Furthermore, the interaction terms of toxic leadership, organizational cynicism, and emotional exhaustion are significant (B = -3.012, p = 0.036). The negative coefficient of the interaction term implies a mitigating impact, indicating that the combined presence of high toxic leadership, high emotional exhaustion, and high organizational cynicism may counterintuitively reduce workplace deviance (t = -2.110). Conclusion These results suggest that while toxic leadership, emotional exhaustion, and organizational cynicism each independently increase workplace deviance, their combined presence may unexpectedly reduce deviant behaviors. Implication for nursing These results highlight the significance of tackling toxic leadership practices and cultivating a positive organizational culture to enhance a healthier work environment and reduce instances of workplace deviance. Healthcare settings should prioritize interventions to improve leadership practices, enhance employee well-being, and cultivate a supportive organizational climate.